Legal Validity and Evidentiary Strength of Online Sales Agreements via WhatsApp - Olivia Rinditamy; Widodo Ramadhana (International Journal of Multidisciplinary Research of Higher Education, 2026)
This study examines the legal validity and evidentiary strength of online sales agreements conducted through WhatsApp, within the framework of Indonesian Civil Law and the Electronic Information and Transactions Law. Using a qualitative normative juridical approach, the research analyzes statutory provisions and conceptual perspectives supported by literature review. The findings indicate that sales agreements via WhatsApp are legally binding as long as they fulfill the validity requirements stipulated in Article 1320 of the Indonesian Civil Code. WhatsApp conversations may serve as admissible electronic evidence under the Electronic Information and Transactions Law, provided they meet the criteria of authenticity, integrity, and accountability. Nevertheless, practical challenges arise from potential data manipulation and difficulties in verifying the parties’ identities. The implications highlight the necessity of supplementary evidence, enhanced public legal literacy, strengthened digital forensic capacity among law enforcement, and adaptive regulatory development to ensure legal certainty in electronic transactions.